PENGUATAN PENDIDIKAN KARAKTER MELALUI KEGIATAN EKSTRAKURIKULER DI SEKOLAH - Dahliyana, Asep (Universitas Pendidikan Indonesia, 2017)
This study aims are to explore and assess information about the development of habituation of character education through the extracurricular activities at school which was held in SMA Negeri 3 Bandung. This research approach is qualitative by the case study method, to reveal and understand the realities that occur intensive and deeply, that related with the phenomenon above. Techniques of collection of data and information through interviews, observation of participant and non-participants, study of documentation, and literature studies. The findings of this study are, the relations of extracurricular activities with the character education is as implementation between knowledge gained in class with the attitude and skills that must be developed in order to have the students form the values of noble character who has become a culture within the school social life.